2015
DOI: 10.1186/s13041-015-0095-0
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of neural and cell cycle-related microRNAs in brain of amyotrophic lateral sclerosis mice at late disease stage

Abstract: BackgroundAmyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease characterized by selective motor neuron degeneration in motor cortex, brainstem and spinal cord. microRNAs (miRNAs) are small non-coding RNAs that bind complementary target sequences and modulate gene expression; they are key molecules for establishing a neuronal phenotype, and in neurodegeneration. Here we investigated neural miR-9, miR-124a, miR-125b, miR-219, miR-134, and cell cycle-related miR-19a and -19b, in G93A-SOD1 mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 59 publications
1
42
0
Order By: Relevance
“…Moreover, the authors found correlative levels of miR-124 and AMPAR in induced pluripotent stem cell-derived neurons from subjects with behavioral variant FTD, supporting investigation of targeting this miRNA for FTD therapy. Several more studies have identified additional alternatively expressed miRNAs in ALS and FTD that could be developed as drug targets or as circulatory biomarkers for ALS [37,69,87,108,133,173,194]. For example, miR-206 was consistently altered during the course disease in SOD1 -Gly93Ala mice and increased in the circulation of a small cohort of ALS patients [173].…”
Section: The Role Of Epigenetic Regulation In Als and Ftdmentioning
confidence: 99%
“…Moreover, the authors found correlative levels of miR-124 and AMPAR in induced pluripotent stem cell-derived neurons from subjects with behavioral variant FTD, supporting investigation of targeting this miRNA for FTD therapy. Several more studies have identified additional alternatively expressed miRNAs in ALS and FTD that could be developed as drug targets or as circulatory biomarkers for ALS [37,69,87,108,133,173,194]. For example, miR-206 was consistently altered during the course disease in SOD1 -Gly93Ala mice and increased in the circulation of a small cohort of ALS patients [173].…”
Section: The Role Of Epigenetic Regulation In Als and Ftdmentioning
confidence: 99%
“…There is growing evidence of the involvement of miRNA deregulation in ALS pathogenesis [207][208][209][210][211]. Changes in miRNA expression have been found in patients and the SOD1 G93A mouse [176,212,213] reflecting a dysfunction of the expressed RNA binding proteins involved in ALS.…”
Section: Microglia May Drive Als Pathophysiologymentioning
confidence: 99%
“…The different expression levels and functional contributions of each miRNA family have been shown in the developmental brain; 14,15,22-24 however, it has been studied less extensively in the adult brain. Abnormal expression of each miRNA family has been reported in adult brains of human patients with Alzheimer disease 25 or schizophrenia (SZ) 26,27 as well as in a mouse model for amyotrophic lateral sclerosis, 28 implying different biological impacts of each miRNA family in the adult brain.…”
Section: Mir-17∼92 In the Brainmentioning
confidence: 99%